Setting a minimum benefit amount in a DC with an underpin occupational pension scheme - Gierusz, Anna (Określenie minimalnej wysokości świadczenia w pracowniczym programie emerytalnym DC z minimalnym świadczeniem, 2018)
In a defined contribution pension scheme risk of an unknown benefit amount is borne by the member. To allow for the risk to be shared between the member and the employer a DC with an underpin can be used. Minimum benefit amount is set in this scheme in advance. Two methods of setting this minimum will be investigated. The first option specifies a minimum benefit amount, calculated given an annual rate of return which should be credited over the whole period of scheme membership. The second one assumes that a minimum rate of return has to be applied to the member’s account every year. The aim of this paper is to compare these two possibilities from the member’s and employer’s point of view. Benefit amount, extra employer contribution amount and frequency were selected as the criteria. It was shown that the second method results in a higher member benefit amount. However, it requires higher and more frequent contributions from the employer
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 541, s. 52-62
Keywords: occupational pension schemes; DC with an underpin; hybrid pension scheme; minimum Benefit; pracownicze programy emerytalne; programy o zdefiniowanej składce; programy hybrydowe; minimalna wysokość świadczenia